The Balance Between Higher Education Autonomy and Public Quality Assurance:Development of the Portuguese System for Teacher Education Accreditation - Bártolo Campos (Arizona State University, 2004)
The accreditation systems of higher education institutions and/or programs are becoming a policy measure used to find a balance between their autonomy and public assurance concerning the quality of the qualifications they award. This article analyses, from the point of view of this balance of power, the process of development of the Portuguese accreditation system aimed at providing public assurance that initial teacher education programs are more driven by social demand, namely by the changing school education needs. This was a political and cultural process rather than a merely rational and technical one. Thus the emergence of the need for, and possibility of, external pressure upon higher education institutions is related to the evolution of several social factors. On the other hand, the implementation of the accreditation system means a significant change for these institutions which implies new practices and comes into conflict with some of their values and with power sharing within and among them and with society. For these reasons a strategy of wide participation of significant stakeholders was deemed more suitable for the formulation, adoption and implementation of this new public policy. The way in which government, the accreditation body, and the significant stakeholders exercised their power in this process influenced the characteristics of the system, the rhythm of its implementation, and the abrupt governmental decision to put it on stand-by, until now.